The main trends in the development of tourism in the 21st century: changing institutional relationships and travel practices - Burak, Tatsiana V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The characteristic of the main directions of changes in the social institution of tourism and the everyday life of traveling are presented. The first tendency of tourism development is the transition from the dominant format of tourism as entertainment to the distribution of educational purposes of tourist travel. The second tendency marks the increasing importance of individually oriented trips, which is associated with the actualisation of travellers’ needs for the experience of symbolic and new co-presence in the search for authentic content of another culture. A logical continuation of the two indicated vectors is the growing number of requests to visit those countries which have growing economies. Another trend that has been probably the leading one throughout the 21st century is the formation of sustainable tourism attitudes. In the conditions of social uncertainty and communication constraints associated with the spread of the coronavirus, there is also an activation of the digital transformation of the tourism sector, not limited to the already familiar forms of Internet communication at the preparatory and final stages of the trip.